2002
DOI: 10.1161/01.hyp.0000016921.50185.7b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mild Exercise on Insulin Sensitivity in Hypertensive Subjects

Abstract: Abstract-Physical exercise increases insulin sensitivity in conditions associated with insulin resistance, such as obesity and diabetes, but little is known in this regard in hypertension. Whether postexercise changes in hemodynamics and/or changes in insulin-induced vasodilatation could contribute to a postexercise increase in insulin sensitivity in hypertensive subjects is unknown. We investigated the effects of acute physical exercise on insulin sensitivity in 10 hypertensive and 10 normotensive subjects du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
2
21
1
Order By: Relevance
“…The increase in blood flow was similar in the exercise and control sessions. This result is similar to the one observed by Rhéaume et al (28), who showed that previous exercise did not change FBF response to glucose infusion. Thus FBF during hyperinsulinemia was even higher after exercise than after rest.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The increase in blood flow was similar in the exercise and control sessions. This result is similar to the one observed by Rhéaume et al (28), who showed that previous exercise did not change FBF response to glucose infusion. Thus FBF during hyperinsulinemia was even higher after exercise than after rest.…”
Section: Discussionsupporting
confidence: 92%
“…The lower MSNA and higher FBF achieved during hyperinsulinemia conducted after exercise in healthy subjects suggest that a single bout of exercise could have important clinical implications, especially in some hyperinsulinemic populations, such as obese (10,25,38) and hypertensive (19,28) patients, who present sympathetic activation (2,22,25,27,38) and blunted vasodilation (3,26,38) during acute hyperinsulinemia induced, for example, by a meal. Nevertheless, it is important to point out that the insulin level achieved after meals is lower than the one used in the present study and occurs concomitantly to hyperglycemia (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in body weight and body fat are known to decrease BP 17) , whereas accumulation of visceral fat will induce insulin resistance 23) . Moreover, it has been reported that mild physical exercise increases the insulin sensitivity in hypertensive subjects 24) . Although parameters concerning insulin sensitivity were not studied in the present study, it is possible that the reduction in insulin resistance through body weight control, and exercise habit might have contributed to the reduction of SBP in the THP group.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of insulin resistance and improvement in endothelial function may also contribute. [19,20] Importantly, this reduction appeared to be independent of the intensity, frequency and type of exercise program. BP reduction was seen in normotensives also and was not inß uenced by initial weight.…”
Section: Increased Physical Activitymentioning
confidence: 92%